1973
DOI: 10.1111/j.1365-2222.1973.tb01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological responses to enzymes of Bacillus subtilis in factory workers and consumers

Abstract: Summary Skin (prick) and serological tests were made with enzyme preparations of Bacillus subtilis in exposed factory workers and potential ‘consumers’. Prick tests with these materials at 10 mg/ml gave positive immediate reactions in twenty‐six out of sixty‐five factory workers. Eighteen of the factory workers were classified as atopic because of allergy to common allergens and fifteen gave positive reactions to the enzymes compared with eleven out of forty‐seven non‐atopic workers. A group of eleven of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 20 publications
2
35
1
Order By: Relevance
“…True subtilisins derived from bacteria are among the best characterized of the subtilase enzyme family. Subtilisin Carlsberg (alcalase) produced by Bacillus licheniformis is frequently used in detergent formulations, and allergic respiratory reactions to alcalase have been reported among exposed factory workers (12,88). More recently, a novel subtilisin homologue with IgE antibody binding properties derived from the fungus Penicillium citrinum was identified (110).…”
Section: Trichophyton Allergens: a Role For Enzymatic Function?mentioning
confidence: 99%
“…True subtilisins derived from bacteria are among the best characterized of the subtilase enzyme family. Subtilisin Carlsberg (alcalase) produced by Bacillus licheniformis is frequently used in detergent formulations, and allergic respiratory reactions to alcalase have been reported among exposed factory workers (12,88). More recently, a novel subtilisin homologue with IgE antibody binding properties derived from the fungus Penicillium citrinum was identified (110).…”
Section: Trichophyton Allergens: a Role For Enzymatic Function?mentioning
confidence: 99%
“…However, the enzymes originating from bacteria and used in the industrial environment (e.g. detergents) can cause asthma or rhinitis with a high prevalence (515,516).…”
Section: Other Mitesmentioning
confidence: 99%
“…Many other high-molecular-weight allergens can induce IgE-mediated rhinitis and asthma: agricultural mites (339-342, 347, 348, 350, 351), coffee beans (598), proteolytic enzymes (515,599,600), other enzymes (601,602), insect dust (577); plants and flowers (603,604).…”
Section: Other Mitesmentioning
confidence: 99%
“…Since that time, more than 25 years of detergent industry experience has provided much information on understanding and managing the effects to humans from exposure to enzyme materials (Pepys et al, 1973(Pepys et al, , 1985Weill et al, 1974;Zetterstrom, 1977). Control of occupational exposure to respirable enzyme dusts has greatly reduced the incidence of immediate hypersensitivity responses to enzymes and the occurrence of enzyme-associated occupational asthma among detergent workers is now a rare event (Juniper and Roberts, 1984;Flood et al, 1985;Sarlo et al, 1990).…”
mentioning
confidence: 99%
“…Control of occupational exposure to respirable enzyme dusts has greatly reduced the incidence of immediate hypersensitivity responses to enzymes and the occurrence of enzyme-associated occupational asthma among detergent workers is now a rare event (Juniper and Roberts, 1984;Flood et al, 1985;Sarlo et al, 1990). In addition, a survey of several thousand consumers has shown that the use of enzymes in laundry products is safe for consumer use (Pepys et al, 1973). Based upon much of these historical data, the American Conference of Governmental and Industrial Hygienists (ACGIH) developed a threshold limit value (TLV) in the workplace for subtilisin A (Alcalase) at 60 ng protein/m 3 (ACGIH, 1990).…”
mentioning
confidence: 99%